Manajemen Kelas Dalam Pembelajaran Pendidikan Agama Buddha Di SDN 2 Karangduwur - Rispatiningsih, Dwi Maryani (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2024)
The aim of this research is to describe the planning of the Buddhist education learning process; to describe the implementation of the Buddhist Education learning process; and to describe the assessment of the Buddhist Education learning process at SDN 2 Karangduwur during the Covid 19 pandemic. This research uses qualitative methods. Implementation of research at SDN 2 Karangduwur, Ayah District, Kebumen Regency. In planning, Buddhist education subject teachers have created a syllabus and prepared lesson plans before carrying out learning activities to serve as a guide in teaching and learning activities. At SDN 2 Karangduwur the average number of students in a class is 24 students and for Buddhists it is a very minority, the total from class 1 to class 6 is 13 students. In managing the learning process, teachers are able to recognize and provide direction to students. When the Covid 19 pandemic occurred, the learning process occurred using one of the applications. Then, during the limited face-to-face meeting held at SDN 2 Karangduwur, all Buddhist students still entered. Remembering that students who are Buddhist are a minority and can keep their distance. In carrying out learning activities in the classroom, the stages that teachers carry out include: carrying out preliminary activities, carrying out core activities and; carry out closing activities. Buddhist education subject teachers evaluate their students by giving homework assignments, assignments done in class, tests, written exams, mid-semester exams, final semester exams, oral questions, and also assessing students' attitudes.